Sargassum polycystum C. Agardh Variations in Morphology of the Brown Seaweed Sargassum polycystum C. Agardh - เชิงสะอาด, สุเมธ; จีรภัทร์ , อนงค์ (KKU Science Journal, 2012)
Morphological variation of the brown alga Sargassum polycystum C. Agardh was investigated from specimens collected from the coast of Samaesan in Chon Buri province. The characteristics of thallus i.e. thallus length, holdfast diameter, blade and vesicle size were measured. Shape and reproductive characters were also examined and drawn with a Camera Lucida. Plants of S. polycystum were yellowish brown in color, holdfasts discoid had a short cylindrical stipe, main axes were terete being obvious rough or spiny. The blade of the secondary order branch was divided into 3 types: 1) large and lanceolate shaped, 2) large and broader than type 1 and 3, and 3) smaller and lanceolate shaped. These three types were significantly different (P < 0.05). Of those three characters, leaf margin serrate, midrib running to near the apex of the blade. Cryptostomata scattered on the surface of the blade. Vesicles varied within a thallus which were divided into 4 characters i.e. 1) ovate shaped 2) ovate to circular shaped with 2 spines on surface 3) ovate with 5-6 spines on surface and 4) ovate with winged-margin and a few cryptostomata. Single or multiple vesicles on the primary and secondary branches; male and female receptacles separated. Male receptacles were long and cylindrical, up to 8 mm long in singularly or in pairs. Female receptacles were cylindrical at lower portion, but slightly compressed at the upper portion, up to 4 mm long. Stolon arising from primary branch differentiated into a new thallus. This study found the vesicles type 4 with winged-margin showing different characters from previous reports of this species in this area.